Effectiveness of Mirror Therapy Combines with Occupational Therapy Program on Upper Extremity Rehabilitation in Stroke - Posawang, Pornsawan Posawang, B.Sc., M.Spec.Ed., Rutteera Ditwichairut, B.Sc., M.A. , Chalinee Khunta, B.Sc., Saranya Kantadetch, B.Sc.; Ditwichairut, Rutteera; Khunta, Chalinee; Kantadetch, Saranya (Journal of The Department of Medical Services, 2021)
Background : Cerebrovascular accident or stroke is a major leading cause of death and long-term disability worldwide. Upper extremity function impairment after stroke is main problem which effects ability to perform activities of daily life as well as the patient’s quality of life. An appropriate and effective upper extremity rehabilitation program, therefore, is very crucial. Objective : The study was designed to determine the effectiveness of mirror therapy (MT) combined with Occupational Therapy (OT) on upper extremity rehabilitation in stroke. Method : Fifty-six post-stroke survivors were assigned to either control group (n=28), or an experimental group (n=28). Twelve intervention sessions were provided for both groups, forty minutes of OT program for control group, and twenty minutes of OT program plus twenty minutes of MT program for experimental group. The recorded measurements consisted of 1) the Fugl Meyer subscores for upper extremity 2) Modified Jebsen Taylor Test of hand function 3) sensation assessment and 4) muscle tone assessment. All participants were assessed before intervention, after the last intervention, 1 and 3 months after last intervention. Results : Both groups demonstrated improvement in upper extremity control and unilateral hand skills, the improvement of these abilities over baseline remained stable longer in experimental group. No differences were observed in sensation and muscle tone measurement. Conclusions : It was concluded that mirror therapy program combined with occupational therapy program (MT+OT) is an effective method for improving upper extremity function in stroke patient.